54 The nlrp3 inflammasome and other related receptors as potential biomarkers in coronary artery disease (cad) and major adverse cardiac events (mace). (5th October 2017) - Gallagher, L; McCusker, M; Chemaly, M; Peace, A; Gibson, M; Bjourson, AJ; Kelly, C; McGilligan, VE
Abstract : Introduction: Coronary artery disease (CAD) is the leading cause of death worldwide caused by atherosclerosis, now believed to be a complex inflammatory process. Mounting data indicates that the Nucleotide-binding domain, leucine-rich containing family, pyrin domain-containing-3 (NRLP3) inflammasome is critical in the pathogenesis and/or regulation of a variety of inflammatory diseases including atherosclerosis. NLRP3 is a multiprotein complex responsible for the activation of capase-1 and proteases required for processing and activating IL-1 b and IL-18. Previous evidence suggests that NLRP3 is activated and regulated by the cannabinoid receptor type 1 (CB1 r) and scavenger receptor, cell surface cluster of differentiation 36 (CD36 r) in response to modified lipoproteins through amplification of inflammation or exposure to oxidised low-density lipoproteins (oxLDL). CB1 r and CD36 r are therefore considered risk factors for atherosclerosis, in the promotion of cholesterol accumulation and release of inflammatory mediators. To date, no study has investigated NLRP3, CD36 r and CB1 r collectively as a potential panel of biomarkers to predict major adverse cardiovascular events (MACE). Purpose: To measure the expression of the NLRP3 inflammasome and associated receptors (CD36 r and CB1 r) and to determine if levels correlate with cardiovascular risk. Methods: Consecutive patients were recruited from the cardiac catheterisation laboratory and outpatient clinics. Group 1 were defined as Very high risk patients (VHR) with a 10-year risk SCORE ≥10% risk of fatal CVD. VHR patients were subdivided in Acute Coronary Syndrome patients (ACS-VHR) and elective percutaneous coronary intervention patients (ELEC-VHR). Group 2 were low risk patients (LR) with a 10-year risk SCORE <1% risk of fatal CVD. Proteins were extracted from a buffy coat preparation using the Mammalian Protein Extraction Reagent (M-PER) and then analysed by western blot. RNA was extracted from the buffy coat and analysed by real time PCR. Results: A total of 60 patients were recruited and the cohort consisted of VHR (n=40), which were divided into ACS-VHR (n=20) and ELEC-VHR (n=20), and LR (n=20). NLRP3 gene expression was higher in VHR compared to LR (0.0284 ± 0.0013 vs. 0.0142 ± 0.0019, p<0.0001). NLRP3 protein levels were also higher in VHR compared to LR (p<0.05). NLRP3 gene and protein levels were particularly higher in ACS-VHR compared to LR (p<0.05). CB1 r protein levels were higher in VHR compared to LR (p<0.01). CD36 R gene expression was not significantly between VHR and LR, however protein levels were significantly different. Conclusion: These results indicate that NLRP3 and CB1 r can potentially differentiate between VHR and LR patients. An ongoing larger cohort study is underway to investigate the utility of NLRP3, CD36 r and CB1 r along with other promising biomarkers to better predict CAD and MACE.